MODEL STUDIES OF FISH EGG AND LARVAL TRANSPORT IN THE KATTEGAT AND THE NORTH ATLANTIC - Pacariz, Selma (2013)
For the early life stages of fish, the dispersal and retention are important factors regarding present and future survivorship, growth and reproduction. The main objective of this thesis is to analyse fish egg and larval transport in two different marine systems, the Kattegat and the North Atlantic. The focus is on two different species, namely Atlantic cod (Gadus morhua) eggs in the Kattegat-Öresund-Belt area and European eel (Anguilla anguilla) leptocephalus larvae in the North Atlantic. The stock of cod in the Kattegat has been severely depleted due to fishery and is presently classified as exhibiting reduced reproductive capacity. It is, therefore, of interest to update information on cod spawning activity and get an understanding of the dispersal of eggs. As to evaluate spawning, data were analysed from dedicated egg surveys in the Kattegat between 2004 and 2006. Genetically identified cod eggs confirmed that cod were spawning in the studied area during the sampling period. The estimated daily egg production was high in the south-eastern part of the surveyed area (~20 eggs m-2 d-1) while it was low (0–5 eggs m-2 d-1) in the central and northern part. This emphasises the importance of the southernmost spawning area in the Kattegat, close to the Öresund. A process oriented model was used to investigate transport of cod eggs and early larvae in relation to egg density as well as how the interannual variation of retention and dispersal is related to the meteorological forcing. The model results clearly indicated that transport is highly dependent on the egg density; lighter eggs are transported northwards, whereas heavier eggs are retained to a larger extent or are transported southwards. An optimum of retention is defined in the density range 1023-1026 kg m-3. Combining the model results of the amount of retention, distribution and sedimentation with observations of vertical distribution of cod-like eggs in the range 1017-1022 kg m-3, suggests that gadoid eggs are mainly retained in the southern Kattegat, but ...